A Retrospective Analysis of the Course of Pregnancy, Childbirth, the Postpartum Period and the Condition of Newborns in Pregnant Women with Abo Immunization (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: ABO immunization; hemolytic disease of the newborn; somatic diseases; placental dysfunction; the blood group; the pregnancy